Some Network Characterizations for Mathematical Programming and Accounting Approaches to Planning and Control. - Charnes, A.; Cooper, W. W. (The Accounting Review, 1967)
Abstract Network characterizations are developed for effecting contacts between accounting and mathematical programming. En route to these objectives some of the customary uses of double entry accounting are altered and related to suitable generalizations of classical network ideas such as the Kirchhoff node conservation laws. Extensions of the usual node-link incidence relations provide a basis for effecting these contacts. Concrete illustrations are supplied including a goods-flow-funds-flow model which is preceded by a simpler example involving a PERT-Critical Path application. The latter is examined in the context of a physical flow of task or project times, while the former suggests haw double entry can be extended to flows that involve a variety of different dimensions. Issues of accounting in different dimensions are thus examined and further issues of accounting for multiple objectives in different and even non-commensurable measures are also indicated. A possibility for joint coordinated uses of programming and accounting in management planning is indicated and amplified and some of the implications for alterations in accounting practice are then examined. Suggestions for further extensions include probabilistic formulations and related risk considerations and evaluations. In an addendum the node-link incidences are further related to node-node incidences in the context of dyadic representations such as are encountered in the transportation type models of linear programming or the spread sheets and articulation statements of double-entry accounting.(n1)